Narrative effectiveness in digital health advocacy: Lessons learned from Casemas.id's storytelling initiative in enhancing national health promotion strategies - Rilfi, Naurah Assyifa; Yulianah, Yulianah (Journal of Community Empowerment for Health, 2025)
Introduction: Storytelling has emerged as a vital tool in public health communication, influencing knowledge, attitudes, beliefs, and behaviors, particularly during the recent pandemic. Rapid dissemination of digital information can foster positive changes in health services and policies. This study examines the role of storytelling in digital health advocacy on Instagram, Indonesia’s second most-used platform. Casemas.id, a youth-led educational initiative launched in 2022, aims to empower the digital community to influence public opinion for positive health system changes.Methods: We utilized quantitative methods, conducting thematic analysis of content structure, message delivery, and audience interaction among 49 Instagram posts from 2022 to 2023. Our findings indicate that public opinion content is the most liked, while practitioner perspective videos achieve the longest viewing durations. Explanatory content garners the most saves, and the highest number of comments originates from public health issues presented as cartoons, illustrations, or memes. Moreover, practitioner perspectives lead in shares.Results: The significant engagement with explanatory content highlights the importance of resonating with audience interests, while cartoons and memes facilitate social interactions, revealing public concerns and misconceptions regarding health. Additionally, the most shared practitioner content reflects trends in the audience's information-giving motives, providing insights for effective dissemination of health information.Conclusion: These findings are relevant for health organizations focused on promoting specific health messages within Indonesia's dynamic digital landscape, offering strategies to enhance storytelling in health promotion and empower the digital community for positive health transformations.